Family violence laws: Traditional narratives and the (in)visibility of lesbian relationships and lesbian-parented families. Issue 3 (3rd July 2019) - (Christina) Hudson, Nina
Abstract: Feminist advocacy and activism over the last 40 years broke historic ground in shining a light on "domestic" or "family" violence, traditionally conceptualized as male violence against female intimate partners and their children. This has resulted in a large body of research, particularly in the United States, United Kingdom, Australia, and similar jurisdictions, around the gendered nature of family violence and violence within heterosexual relationships and heterosexual-parented families. As a consequence, the predominant narrative—in political, policy, and advocacy settings—is largely heteronormative. Less research has focused on family violence in non-heterosexual relationships. The data that do exist have employed different methodological approaches and there are limitations on the extent to which they can be compared to the data on violence within heterosexual relationships. However, the existing research does demonstrate that family violence within lesbian, gay, bisexual, transgender, and intersex (LGBTI) communities is a significant issue. Even so, the current narrative does not acknowledge this, and predominantly reflects heterosexual norms of intimate relationships and family structures in society. LGBTI relationships are described as "invisible" in policy and practice responses to family violence, due to the failure to acknowledge violence in such communities. This article explores these claims in relation to lesbian relationships in the context of Australian legislative responses to family violence. It considers the extent to which family violence laws in two Australian jurisdictions recognize and frame lesbian identity in intimate relationships and lesbian-parented families. This is considered in light of the emerging conceptualization of family violence in lesbian relationships and lesbian-parented families, as evidenced by the wider scholarly literature on the nature and dynamics of such violence.